2016
DOI: 10.1371/journal.pone.0158644
|View full text |Cite
|
Sign up to set email alerts
|

The Invalidation of HspB1 Gene in Mouse Alters the Ultrastructural Phenotype of Muscles

Abstract: Even though abundance of Hsp27 is the highest in skeletal muscle, the relationships between the expression of HspB1 (encoding Hsp27) and muscle characteristics are not fully understood. In this study, we have analysed the effect of Hsp27 inactivation on mouse development and phenotype. We generated a mouse strain devoid of Hsp27 protein by homologous recombination of the HspB1 gene. The HspB1-/- mouse was viable and fertile, showing neither apparent morphological nor anatomical alterations. We detected a gende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…However, in skeletal muscle, HSPB1 loss decreases resistance to repetitive muscle fatigue and HSPB1 −/− mice display decreased voluntary running 10 . Notably, macroscopic examination of soleus muscle tissue from HSPB1 −/− mice failed to reveal any structural alterations and only electron microscopy was able to detect minor myofibril changes 39 . Since in situ hybridization studies on HSPB1 expression in mouse tissues identified elevated mRNA levels in the arterial system 6 and a preliminary microarray experiment from MEFs lacking HSPB1 demonstrated altered elastin levels (data not shown), we examined whether loss of HSPB1 adversely affected arterial structure and function in septic mice.…”
Section: Discussionmentioning
confidence: 98%
“…However, in skeletal muscle, HSPB1 loss decreases resistance to repetitive muscle fatigue and HSPB1 −/− mice display decreased voluntary running 10 . Notably, macroscopic examination of soleus muscle tissue from HSPB1 −/− mice failed to reveal any structural alterations and only electron microscopy was able to detect minor myofibril changes 39 . Since in situ hybridization studies on HSPB1 expression in mouse tissues identified elevated mRNA levels in the arterial system 6 and a preliminary microarray experiment from MEFs lacking HSPB1 demonstrated altered elastin levels (data not shown), we examined whether loss of HSPB1 adversely affected arterial structure and function in septic mice.…”
Section: Discussionmentioning
confidence: 98%
“…HSP27-encoded by HspB1 is constitutively present in a wide variety of tissues and in many cell lines. The abundance of HSP27 is greater in skeletal muscle, indicating an important role for muscle physiology ( Kammoun et al, 2016 ) and thus for muscle to meat conversion ( Picard & Gagaoua, 2017 ; Picard, Gagaoua & Hollung, 2017b ). An earlier study by our group showed that it is at a crucial hub in a functional network involved in beef tenderness ( Guillemin et al, 2011a ).…”
Section: Discussionmentioning
confidence: 99%
“…The absence of myofiber defect was unexpected, since HSPB8 participates in myofibril stabilisation through the CASA complex [ 38 , 79 , 80 ]. Furthermore, depletion of Hspb1, another member of the sHSP family whose mutant form has also been associated with myopathy, leads to myofiber ultrastructural defects [ 46 ]. Although the Hspb8 −/− myofibers did not undergo atrophy and degeneration, they presented an accumulation of abnormally patterned mitochondria.…”
Section: Discussionmentioning
confidence: 99%